2010
DOI: 10.1126/science.1190371
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of 50 Human Exomes Reveals Adaptation to High Altitude

Abstract: Residents of the Tibetan Plateau show heritable adaptations to extreme altitude. We sequenced 50 exomes of ethnic Tibetans, encompassing coding sequences of 92% of human genes, with an average coverage of 18X per individual. Genes showing population-specific allele frequency changes, which represent strong candidates for altitude adaptation, were identified. The strongest signal of natural selection came from EPAS1, a transcription factor involved in response to hypoxia. One SNP at EPAS1 shows a 78% frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,514
8
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,404 publications
(1,608 citation statements)
references
References 26 publications
30
1,514
8
10
Order By: Relevance
“…Statistics d was obtained either summing across all pairs of populations, that is, a global measure of differentiation, or between population k and their three nearest populations in terms of lowest F ST . This latter statistics is similar to that proposed by Yi et al (2010), and should be more powerful to identify selection than is Akey's statistics (Equation (1)) as it provides a direction to the allele frequency trajectory and reduces noise relative to the global test, where all population pairs are averaged. All populations with N44 were analyzed individually.…”
Section: Resultsmentioning
confidence: 99%
“…Statistics d was obtained either summing across all pairs of populations, that is, a global measure of differentiation, or between population k and their three nearest populations in terms of lowest F ST . This latter statistics is similar to that proposed by Yi et al (2010), and should be more powerful to identify selection than is Akey's statistics (Equation (1)) as it provides a direction to the allele frequency trajectory and reduces noise relative to the global test, where all population pairs are averaged. All populations with N44 were analyzed individually.…”
Section: Resultsmentioning
confidence: 99%
“…Finding evidence for parallel or convergent adaptation provides strong evidence for a gene's adaptive importance, informs our understanding of constraints to adaptive evolution, and may improve our ability to predict adaptive responses to selection [29,30]. Population genetic approaches have revealed several examples of convergent local adaptation at the molecular level: within the threespine stickleback (Gaterosteus aculeatus) the EBT locus has been involved in repeated adaptation to freshwater habitats [31], two species of European spruce harbor adaptive latitudinal clines at Ft2 and GI genes [32], and EPAS1 and HBB genes show patterns of high altitude adaptation in both dogs [33] and Tibetan humans [34]. Chen et al [32,36] identified a total of 18 genes harboring SNPs with signatures of latitudinal adaptation in the two species but only 2 genes were detected in both species, and Wang et al [33] identified 14 genes with strong signatures of high altitude adaptation in dogs but only 2 targeted in both dogs and humans.…”
Section: Is Local Adaptation Convergent At the Molecular Level?mentioning
confidence: 99%
“…of homozygosity are expected to be the more powerful methods applied to detect these signatures (Yi et al, 2010;Garud et al, 2013;Messer and Petrov, 2013).…”
Section: Moving Towards An Autosomal and Paternal Marker-based Definimentioning
confidence: 99%